2004
DOI: 10.2320/matertrans.45.2794
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Magnetoimpedance in Fe<SUB>74.5&minus;<i>x</i></SUB>Cu<SUB><i>x</i></SUB>Nb<SUB>3</SUB>Si<SUB>13.5</SUB>B<SUB>9</SUB> As Cast Ribbons

Abstract: With increasing Cu content x in Fe 74:5Àx Cu x Nb 3 Si 13:5 B 9 as cast ribbons, an enhancement of magnetoimpedance can be observed. The magnetoimpedance ðZðHÞ À Zð0ÞÞ=Zð0Þ for Fe 72 Cu 2:5 Nb 3 Si 13:5 B 9 as cast ribbon reaches À35% under a dc field H ¼ 7162 A/m at a frequency f ¼ 1 MHz. The longitudinal magnetoimpedance effect in Fe 74:5Àx Cu x Nb 3 Si 13:5 B 9 as cast ribbons is connected with the variation of transverse permeability. The grain size of -Fe(Si) in Fe 72 Cu 2:5 Nb 3 Si 13:5 B 9 as cast ribbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…With increasing Cu content, the amount of Cu clusters as nucleation sites of -Fe(Si) increases, [2][3][4] improving the nanocrystallization of Fe 74:5Àx Cu x Ta 3 Si 13:5 B 9 as-quenched ribbons. The phenomenon that the excess Cu addition reduces the volume fraction of precipitated -Fe(Si) in the as-quenched ribbons is connected with the reduction of effective number density of nucleation sites for -Fe(Si).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing Cu content, the amount of Cu clusters as nucleation sites of -Fe(Si) increases, [2][3][4] improving the nanocrystallization of Fe 74:5Àx Cu x Ta 3 Si 13:5 B 9 as-quenched ribbons. The phenomenon that the excess Cu addition reduces the volume fraction of precipitated -Fe(Si) in the as-quenched ribbons is connected with the reduction of effective number density of nucleation sites for -Fe(Si).…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] The Cu addition in as-quenched ribbons improves the nucleation of -Fe(Si) during rapid solidification, [2][3][4] similar to the case of annealed ribbons.…”
Section: Introductionmentioning
confidence: 99%
“…14,15) Recently, it was found that magnetic soft Fe-Cu-Nb-Si-B and Fe-Zr-B-Cu nanocrystalline materials with -Fe(Si)/-Fe nano-grains, showing GMI effect, can be obtained directly from the meltspinning without additional annealing processes. 16,17) In the present work, the giant magnetoimpedance in Fe 84 Nb 3:5 -Zr 3:5 B 9Àx Cu x as cast ribbons was reported. Results indicated that similar to nanocrystalline Fe-Cu-Nb-Si-B 16) and Fe-Zr-B-Cu, 17) Fe-(Nb,Zr)-B-Cu nanocrystalline ribbons with large GMI effect can also be directly fabricated through meltspinning technique.…”
Section: Introductionmentioning
confidence: 99%
“…16,17) In the present work, the giant magnetoimpedance in Fe 84 Nb 3:5 -Zr 3:5 B 9Àx Cu x as cast ribbons was reported. Results indicated that similar to nanocrystalline Fe-Cu-Nb-Si-B 16) and Fe-Zr-B-Cu, 17) Fe-(Nb,Zr)-B-Cu nanocrystalline ribbons with large GMI effect can also be directly fabricated through meltspinning technique. The high Cu addition in NANOPERM not only enhances the nucleation of -Fe in as cast ribbon, but also reduces its grain size.…”
Section: Introductionmentioning
confidence: 99%